Safe injection, infusion and medication-vial practices at a tertiary care centre: a quality improvement initiative - Kottapalli, Pragathi; Podduturi, Naveen Chander Reddy; Aswini, Ganta; Jyothi, Somisetty; Naveen, Admala (German Medical Science GMS Publishing House, 2023)
Introduction: There is a risk of transmission of viruses and microbial pathogens during routine health care procedures due to improper injection, infusion, and medication-vial practices. Unsafe practices lead to outbreaks of infection resulting in unacceptable and devastating events in patients. The present study was undertaken to assess the compliance of nurses with safe injection and infusion practices in our hospital and to identify staff education requirements in relation to the safe-injection and infusion practices policy.Methods: Baseline data were collected and high risk areas were identified on this basis, a quality improvement project was implemented by infection control team. FOCUS PDCA methodology was used to conduct the improvement process. The study was performed from March to September 2021. An audit checklist based on the CDC guidelines was used for monitoring compliance with safe injection and infusion practices. Results: Poor compliance with safe injection and infusion practices in few clinical areas at baseline. During the pre-intervention period, non-compliance was mainly seen with the following elements: aseptic technique (79%), rubber septum disinfected with alcohol (66%), labelling of all IV lines and medications with date and time (83%), compliance with multidose-vial policy (77%), use of multidose vials for single patient (84%), safe disposal of sharps (84%), using trays instead of clothing/pockets to carry medications (81%).There was significant improvement in compliance with the following elements of safe injection and infusion practices in the post-intervention period: aseptic technique (94%), rubber septum disinfected with alcohol (83%), compliance with multidose-vial policy (96%), use of multidose vials for single patient only (98%), safe disposal of sharps (96%).Conclusion: Adherence to safe injection and infusion practices is very important to prevent outbreaks of infection in health care settings.